Pengaruh Social Media Marketing, Influencer Marketing dan Promosi Waktu Terbatas Terhadap Keputusan Pembelian pada Tomoro Coffee di Kota Samarinda - Theodore Farrel Ouby Saleh Putra; Zainal Abidin; Melda Aulia Ramadhani (Indo Publishing, 2026)
This study aims to analyze the influence of social media marketing, influencer marketing, and limited-time promotions on purchasing decisions at Tomoro Coffee in Samarinda City. The research employed a quantitative approach using purposive sampling techniques involving 140 respondents who had purchased Tomoro Coffee products. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with SPSS assistance. The results showed that simultaneously social media marketing, influencer marketing, and limited-time promotions significantly influenced purchasing decisions. Partially, social media marketing had a positive but insignificant effect on purchasing decisions. Meanwhile, influencer marketing and limited-time promotions had a positive and significant effect on purchasing decisions. Influencer marketing became an effective factor in increasing consumer trust through influencer credibility, while limited-time promotions created a sense of urgency that encouraged consumers to make immediate purchases. This study implies that Tomoro Coffee needs to improve more innovative digital marketing strategies and maximize the use of influencers and limited-time promotions to enhance consumer purchasing decisions.